2019
DOI: 10.1123/ijspp.2018-0842
|View full text |Cite
|
Sign up to set email alerts
|

Alternate-Day Low Energy Availability During Spring Classics in Professional Cyclists

Abstract: Purpose: To assess energy and carbohydrate (CHO) availability and changes in blood hormones in 6 professional male cyclists over multiple single-day races. Methods: The authors collected weighed-food records, power-meter data, and morning body mass measurements across 8 d. CHO intakes were compared with contemporary guidelines. Energy availability (EA) was calculated as energy intake minus exercise energy expenditure, relative to fat-free mass (FFM). Skinfold thickness and blood metabolic and reproductive horm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 24 publications
(18 reference statements)
1
31
0
Order By: Relevance
“…While the time-course of changes as a result of LEA remains somewhat unknown and is likely to vary between various body systems, laboratory studies have shown impairments in as little as 4-5 days [45]. On the contrary, a recent report in professional male cyclists showed that very brief (< 24 h) exposures to extreme LEA (< 15 kcal/kg FFM/day) over an 8-day single-day racing period did not impair sex and metabolic hormone concentrations when alternated with days of > 45 kcal/kg FFM/day EA [32]. While the (male) endocrine system might be more resilient to acute and brief changes in EA, emerging evidence suggests that brief periods of LEA can impair sports performance indirectly as a result of decreased glycogen stores [40] and increased risk for illness [16], which will have residual effects beyond the success during the TDS.…”
Section: Energy Availability In XC Skiersmentioning
confidence: 95%
See 3 more Smart Citations
“…While the time-course of changes as a result of LEA remains somewhat unknown and is likely to vary between various body systems, laboratory studies have shown impairments in as little as 4-5 days [45]. On the contrary, a recent report in professional male cyclists showed that very brief (< 24 h) exposures to extreme LEA (< 15 kcal/kg FFM/day) over an 8-day single-day racing period did not impair sex and metabolic hormone concentrations when alternated with days of > 45 kcal/kg FFM/day EA [32]. While the (male) endocrine system might be more resilient to acute and brief changes in EA, emerging evidence suggests that brief periods of LEA can impair sports performance indirectly as a result of decreased glycogen stores [40] and increased risk for illness [16], which will have residual effects beyond the success during the TDS.…”
Section: Energy Availability In XC Skiersmentioning
confidence: 95%
“…Several reports exist on total daily energy expenditure in other endurance sports such as road cycling, These studies report total daily energy expenditures of up to 6071 and 7815 kcal/day in male cyclists during an average stage and a mountain stage of a cycling grand tour [60], respectively; meanwhile race energy expenditures of up to 5184 kcal were reported in male cyclists during single-day classic [32]. On the contrary, few studies have attempted to quantify energy expenditure and EI in elite XC skiers.…”
Section: Daily Energy Expenditure In XC Skiersmentioning
confidence: 99%
See 2 more Smart Citations
“…Research has suggested that short-term perturbations in EA do not appear to have as severe an impact on male athletes compared to female athletes [7,33]. However, recent research has suggested that extremely low EA, or even within day periods of LEA, can still result in measurable disturbances in hormone levels in male athletes after only eight days of intermittent LEA [34].…”
Section: Measured Energy Availability In Para-athletesmentioning
confidence: 99%